Psychometric properties of an Arabic translation of the 13-item short mood and feelings questionnaire- parent version (SMFQ-P) to screen for depression in children - Amir Noureddine; Diana Malaeb; Sami El Khatib; Mariam Dabbous; Fouad Sakr; Amira Mohammed Ali; Feten Fekih-Romdhane; Souheil Hallit; Sahar Obeid (BMC Psychiatry)
Abstract Background Understanding the connection between parental wellbeing and its impact on childhood depression is crucial in order to develop targeted interventions and support systems that can mitigate potential long-term effects on mental health. This study focuses on examining the properties of an Arabic translation of a questionnaire called Short Mood and Feelings Questionnaire Parent Version (SMFQ-P) as a preliminary step toward validating a culturally relevant screening tool for childhood depression in Lebanon. Methods A total of 502 parents, recruited through a snowball method, took part in the survey with an age of 36.24 years (SD ± 8.29). Among them 74.5% were females 88.8% were married and 72.9% had completed university level education. The children’s mean age was 7.95 ± 1.14 years. The SMFQ-P was evaluated using confirmatory factor analysis (CFA), reliability measures, and correlations with parental distress using the Depression Anxiety Stress Scale-8 (DASS-8). Results Confirmatory factor analysis (CFA) demonstrated an excellent fit for the one-factor model of SMFQ-P scores (RMSEA = 0.059, 90% CI [0.049, 0.070]; SRMR = 0.034; CFI = 0.967; TLI = 0.960), with standardized factor loadings ranging from 0.58 to 0.82. Male parents reported more depression in their child than female parents (p = .016). Parental distress levels (r = .60, p < .001) correlated strongly with SMFQ-P scores, suggesting indirect concurrent validity. Conclusion The SMFQ-P shows promise as a screening tool for childhood depression, offering preliminary evidence of its reliability and validity in the Lebanese context. Limitations, including reliance on parent-reported distress and the lack of a direct child-report validation, should be addressed in future studies.